1997
DOI: 10.1038/sj.ejcn.1600449
|View full text |Cite
|
Sign up to set email alerts
|

A 7-day activity diary for assessment of daily energy expenditure validated by the doubly labelled water method in adolescents

Abstract: Objectives: To validate the use of an activity diary and predicted BMR for assessment of daily total energy expenditure (TEE) and physical activity level (PAL TEE/BMR) in adolescents. Design: TEE and PAL estimated from activity diary records kept for seven days and BMR predicted from age, gender and body weight were compared with the results of doubly labelled water (DLW) measurements and indirect calorimetry performed during the same time period. Setting: The Unit of Paediatric Physiology of the Department of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
120
4
12

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(144 citation statements)
references
References 14 publications
6
120
4
12
Order By: Relevance
“…Using the Bouchard diary, categorical values 1-3 represent IA (median MET value o2.8 METs) and values 6-9 represent MVPA (median MET value X4.8 METs) (1 MET ¼ 3.5 ml O 2 /kg/min or 1 kcal/kg/h). The repeatability of this activity diary has previously been determined (r ¼ 0.97) (Bouchard et al, 1983) and a version has been validated with the doubly labeled water method in a sample of 50 adolescents over a 7-day-period with a mean difference in TEE of 1.2% between the two methods (Bratteby et al, 1997).…”
Section: Participantsmentioning
confidence: 99%
“…Using the Bouchard diary, categorical values 1-3 represent IA (median MET value o2.8 METs) and values 6-9 represent MVPA (median MET value X4.8 METs) (1 MET ¼ 3.5 ml O 2 /kg/min or 1 kcal/kg/h). The repeatability of this activity diary has previously been determined (r ¼ 0.97) (Bouchard et al, 1983) and a version has been validated with the doubly labeled water method in a sample of 50 adolescents over a 7-day-period with a mean difference in TEE of 1.2% between the two methods (Bratteby et al, 1997).…”
Section: Participantsmentioning
confidence: 99%
“…In addition, to our knowledge information on the time spent on different categories of physical activities has only been obtained from four studies carried out with 10 -15-y-old children from activity diaries (Armstrong et al, 1990;Bratteby et al, 1997a;Henry et al, 1999;Ekelund et al, 2000). Furthermore, approximate costs of activities in adolescents have been derived from measurements in adults, and adapted for a diary of activities (Bouchard et al, 1983) or the DLW method (Bratteby et al, 1997b). Unfortunately, the estimated energy costs of high or very high intensity manual work and sport differed greatly between the two sets of data.…”
Section: Introductionmentioning
confidence: 99%
“…Had we applied the 30% increase in energy cost to all active activities, 94% of subjects would have shown differences of less than 712.8%. Many other studies have reported acceptable factorial estimates for groups but less acceptable estimates for individuals (Bratteby et al, 1997;Morio et al, 1997;Withers et al, 1998).…”
Section: Resultsmentioning
confidence: 94%
“…FEE was underestimated by 14.6% relative to DEE, but this was improved to 5.1% (P ¼ 0.071) when FEE was adjusted for EPOC and TEF. Some studies have also found factorial underestimation of daily EE (Haggarty et al, 1994;Leonard et al, 1997), but others have reported overestimation (Alfonzo-Gonzalez et al, 2004;Walsh et al, 2004), or no difference between FEE and DEE measures (Bratteby et al, 1997;Jones et al, 1997;Morio et al, 1997;Withers et al, 1998;Seale et al, 2002). Such discrepancies are very likely owing to differences in methods used to determine BMR and energy costs of activities, the number of activity categories used and the accuracy of estimates or records of time spent in activities, all of which affect the precision of factorial methods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation